Personalized Medicine in Ovarian Cancer: A Perspective From Mexico - Fernández Garza, Luis E.; Domínguez Vigil, Irma Guadalupe; Garza Martínez, José; Valdez Aparicio, Erick A.; Barrera Barrera, Silvia A.; Barrera Saldaña, Hugo Alberto (Elmer Press, 2021)
Ovarian cancer (OC) represents a serious health problem worldwide. In Mexico, most OC patients are detected at late stages, consequently making OC one of the leading causes of death in women after reaching puberty. Personalized medicine (PM) provides an individualized therapeutic opportunity for treating each patient relying on “omic” tools to match the correct drug with the specific pathogenic genomic signature. PM can help predict the best therapeutic option for each affected woman suffering from OC. In recent years, Mexico has made contributions to the PM of OC; however, it still has a long way to go for its full implementation in the country’s health system.